Supercorp how vanguard companies create innovation, profits, growth, and social good - Kanter, Rosabeth Moss (New York Crown Business, 2009)
Discusses the concept of "vanguard companies" whose mission combines a social conscience along with the ability to deliver on customers' needs better than competitors, citing IBM's expertise in India following the 2006 tsunami and earthquake as an example.
Includes bibliographical references (p. 275-303) and index.
Keywords: Social responsibility of business; Corporations -- Social aspects